Application of homotopy-perturbation method to nonlinear population dynamics models - Chowdhury, Md. Sazzad Hossien; Hashim, Ishak; Abdulaziz, O. (Elsevier, 2007)
In this Letter, the homotopy-perturbation method (HPM) is employed to derive approximate series solutions of nonlinear population dynamics models. The nonlinear models considered are the multispecies Lotka–Volterra equations. The accuracy of this method is examined by comparison with the available exact and the fourth-order Runge–Kutta method (RK4).